Meta-analysis on intervention effects of exercise on Chinese children and adolescents with mobile phone dependence - Chen, Long; Ren, Yilin; Zhu, Pingting; Yang, Yahui; Zhu, Fengshu (Frontiers in Psychology, 2025)
ObjectiveThis study aims to examine which exercise regimens may have a stronger intervention effect and assess the impact of exercise on children’s and teenagers’ dependence on mobile phones using a meta-analysis system.MethodsFrom the library’s founding until December 2023, we searched the databases of China Knowledge, Wanfang, Wipro, PubMed, Web of Science, and the Cochrane Library for experimental studies on the effects of exercise on children’s and adolescents’ dependence on mobile phones. We also evaluated the literature’s quality using the Cochrane Handbook and performed meta-analyses using the RevMan 5.4 software. Using the standardized mean difference (SMD) and 95% confidence interval (CI) as the primary effect indicators, a meta-analysis was conducted utilizing RevMan 5.4 software. The protocol of this systematic review was registered in PROSPERO (CRD42024543710).Results(1) Aerobic exercise showed a significant intervention effect on mobile phone dependence in children and adolescents in the intervention content subgroups but was not statistically significant in the combined exercise subgroups. (2) Exercise demonstrated a large effect size intervention effect on mobile phone dependence in children and adolescents. (3) Regarding mobile phone dependence in children and adolescents, the intensity of the intervention was divided into three subgroups: medium, moderate to high, and low. (4) The greatest intervention effect on mobile phone dependence was observed with a three-times-weekly intervention frequency. (5) Exercise lasting between 8 to 30 weeks showed a positive intervention effect on mobile phone dependence, with the most effective intervention occurring around 12 weeks. (6) The following order reflected the effect of the intervention duration on children and adolescents’ mobile phone dependence: 40–45 min, 20–30 min, ≥90 min, and 60 min.Conclusion(1) Children and teenagers with cell phone addictions can benefit from exercise in reducing their symptoms; (2) the content, intensity, period, frequency and duration of exercise all exert a varying degree of influence on the intervention effect of exercise on mobile phone dependence in children and adolescents. Moderate-intensity aerobic exercise, lasting for 40–45 min three times a week for a total of approximately 12 weeks, is more likely to achieve the desired intervention effect of improving mobile phone dependence in children and adolescents.